Two fluorescence lifetime components reveal the photoreduction dynamics of monolayer graphene oxide. (November 2016) - He, Wenjun; Qin, Chengbing; Qiao, Zhixing; Zhang, Guofeng; Xiao, Liantuan; Jia, Suotang
Abstract: Photoreduction of graphene oxide is a flexible and green method to produce high-quality large-scale reduced graphene oxide. However, the dynamics of photoreduction of monolayer graphene oxide on the substrate, which plays a key role in practical applications, is still unclear. Here we perform fluorescence lifetime measurements to develop and understand this process by using time-correlated single photon counting technology. Two fluorescence lifetime components have been determined to reveal the dynamics and structural evolutions of graphene oxide during laser irradiation. The component with shorter lifetime, the fluorescence intensity of which is barely dependent on the laser irradiation, is assigned to confined sp 2 clusters. The component with longer lifetime that is strongly sensitive to the irradiation time is attributed to hydroxyl groups. The present study offers a useful guidance for optoelectronic devices based on monolayer reduced graphene oxide.